Tests on the punching resistance of flat slabs with unbalanced moments. (1st October 2019) - Ferreira, Maurício de Pina; Oliveira, Marcos Honorato; Melo, Guilherme Sales S.A.
Highlights: Punching strength of flat slabs with unbalanced moments was investigated. The transference of moments affected the failure surface of slabs without studs. In some slabs failure was initiated by loss of anchorage in the lower stud heads. Studs placed up to 1.2d from the column face were fully activated before failure. ACI, EC2 and MC10 presented conservative strength predictions for the tested slabs. Abstract: This paper presents results of tests on eight reinforced concrete slab-column connections without and with shear reinforcement under monotonic concentric and eccentric loading. The slabs were square, with sides of 2.5 m, 180 mm thick, and were centrally supported on square column stubs with sides of 300 mm. The slabs were cast with concrete with a mean compressive strength of 49 MPa, with constant flexural reinforcement ratio (1.5%) and with different amounts of double-headed studs as shear reinforcement. All the slabs failed by punching shear and their flexural and shear responses, as well as their ultimate punching strengths, are described and discussed by comparing the experimental observations with theoretical results obtained following the recommendations presented by ACI 318, Eurocode 2 and fib Model Code 2010.